Using Peer Editing and Peer Feedback Techniques in Writing to Private University Students - Tridinanti, Gaya; Roni, Rusman; Sari, Farnia (FKIP Universitas Lampung, 2020)
Using Peer Editing and Peer Feedback Techniques in Writing to Private University Students. Objectives: this reserach is to find out whether there was any significant difference betweeen the students are taught by using Peer Editing and Peer Feedback Technique. Methods: Quasi-Experimental method was used by providing two groups as an experimental group and control group. The total of students from both groups was 100 students. The data were analyzed by paired sample t-test and independent sample t-test. Findings: The result of paired sample ttest innexperimental and control group showed that value of p-value was .000. At the signicance level p > 0.05 for two tailed test. Conclusion: the use of Peer Editing and Peer Feedback technique can improve students’ in writing narrative text. Keywords: peer-editing technique, peer feedback technique, writing skill DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202001